The Noise of Time: navigating the periphery of anthropological experimental essay film. - Guzmán, Rubén Hector (2019)
Fil: Guzmán, Rubén. Universidad Nacional de Río Negro. Laboratorio Texto, Imagen y Sociedad (LabTIS). Río Negro, Argentina.